Aktivitas Hepatoprotektif Ekstrak Etanol Daun Kucing-kucingan Acalypha indica L.) pada Tikus Putih (Rattus Novergicus) yang Diinduksi Parasetamol - T Armansyah TR; Amalia Sutriana; Dwinna Aliza; Henni Vanda; erdiansyah rahmi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
The  research  has  been  conducted  to  determine  hepatoprotective  effect  of  ethanolic  extract  of Acalypha  indica  L.  leaves  on  rats  (Rattus  novergicus)  induced  with  paracetamol.  The  study  was performed  following  a  completely  randomized  design, using  45 male  rats  (Rattus  novergicus)  divided into  5  groups.  Rats  in  group  1  (K1)  were  given  CMC  1  %  for  7  days  and  followed  by  aquadest administration 8 hours post given CMC on day 7. Group 2 was given CMC 1 % for 7 days and treated with paracetamol at dose 2,5 g/kg BW 8 hours post given CMC on day 7. Groups 3 (K3), 4 (K4), and 5 (K5) were pretreated with ethanolic extract of Acalypha indica L.  leaves at the dose of 50, 100, and 200 mg/kg BW for 7 days respectively, followed by paracetamol administration at the dose of 2.5 g/kg BW in the  next  8  hours  on  day  7. Paracetamol  hepatotoxicity  and  extracts  activity were measured  based  on SGPT and SGOT activity level on day 0, 8 hours after  last administration of  extract on day 7, and 24 hours post paracetamol administration. Data were analyzed using one way ANOVA. The result showed that  the  administration  of  ethanolic  extract  of Acalypha  indica  leaves  at  the  dose  of  50,  100,  and  200 mg/kg BW was  significantly  reduced SGPT  and SGOT  level  (P<0,05)  in  rats  that were  induced with paracetamol. Based on the results of SGPT and SGOT serum activity, it can be concluded that ethanolic extract of Acalypha indica L. potential as hepatoprotective agent.